Baker's biographical dictionary of musicians - Slonimsky, Nicolas 1894-1995; Slonimsky, Nicolas 1894-1995; Kuhn, Laura Diane (Gale virtual reference library, 2001)
Covers all musical genres, including popular, jazz, country, and rock, as well as classical. Offers the most comprehensive and authoritative information on the musicians, along with insightful evaluations of their contributions to the musical world.